Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1002/cncr.20323
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and drinking can induce p15 methylation in the upper aerodigestive tract of healthy individuals and patients with head and neck squamous cell carcinoma

Abstract: BACKGROUND The consumption of tobacco and alcohol has been implicated in the development of head and neck squamous cell carcinoma (HNSCC). Promoter methylation of tumor suppressor genes is common in HNSCC. In this study, the authors evaluated the effects of tobacco and alcohol on p15 gene methylation of cells in cells from the mouth and throat of physically healthy individuals and patients with HNSCC. METHODS The study participants were divided into 3 groups, including a group of 37 healthy nonsmokers and nond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 18 publications
3
52
0
5
Order By: Relevance
“…Higher GSTT1 [-] and GSTM1 [-] polymorphism frequencies were observed by Drummond et al 21,22 in Brazilian smokers with oral cavity squamous cell carcinoma (81.8% for GSTT1 [-] and 70.5% for GSTM1 [-] 15,20,22,44 which was not seen in other studies. 5,16,37,39,41,43,46 The combination of these higher risk and null genotypes has also been observed in this type of carcinoma.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Higher GSTT1 [-] and GSTM1 [-] polymorphism frequencies were observed by Drummond et al 21,22 in Brazilian smokers with oral cavity squamous cell carcinoma (81.8% for GSTT1 [-] and 70.5% for GSTM1 [-] 15,20,22,44 which was not seen in other studies. 5,16,37,39,41,43,46 The combination of these higher risk and null genotypes has also been observed in this type of carcinoma.…”
Section: Discussionmentioning
confidence: 81%
“…1 The most frequent histological type is the squamous cell carcinoma, which is found in over 90% of cases, [2][3][4] and is usually associated with the use of alcohol and tobacco. [5][6][7][8][9] It is known that cigarette smoke is a complex mixture of over 4,000 substances, of which at least 40 are carcinogenic, initiating or promoting tumors in animals. 10 Levels of electrophilic products launched into the bloodstream depend on the action of enzymes involved in biometabolism, which includes activation (Phase I) and detoxification (Phase II) of chemical compounds.…”
Section: Introductionmentioning
confidence: 99%
“…As the consumption of tobacco and alcohol has been implicated in the methylation of tumor suppressor gene p15 [48], it indicates the need to exclude the effect of smoking and drinking on methylation. We found that the five…”
Section: S H O R T C O M M U N I C a T I O N F Wu Et Al Ijomeh 2013mentioning
confidence: 99%
“…Cell cycle regulation, which is coordinated by cyclin-dependent kinases, its binding partners, and the inhibitory molecules such as p16, pRb, and p15 have been widely studied in oral cancer (Chang et al, 2004;Nakahara et al, 2001;Lee et al, 2004;Soni et al, 2005). Cellular signal transduction involves the conversion of one signal or stimulus (mechanical or chemical) to another.…”
Section: Dna Methylation and Gene Dysregulation In Oral Carcinogenesismentioning
confidence: 99%
“…It is widely accepted that the aberrant DNA methylation changes can be induced by both cigarette smoke and alcohol. Alcohol consumption and smoking induced the hypermethylation of p15 in the upper respiratory tract cells (Chang et al, 2004), while the hypermethylation of MGMT, p16 and DAPK was associated with tobacco-chewing induced oral cancers (Vuillemont et al, 2004). A correlation was also found between cigarette smoking and the hypermethylation of CDH1, RARbeta and FHIT (Van Engeland et al, 2003).…”
Section: Epigenetic Changes In Laryngeal Cancermentioning
confidence: 99%